Adoption of blended learning in higher education: faculty perception and evaluation (Revista Electrónica Calidad en la Educación Superior, 2023)
The COVID-19 pandemic has had a major impact worldwide. It affected not only public health but also the economy and education. This study focused on examining the relationship between various teacher factors in addressing student learning under pandemic conditions. It made use of the opportunities, skills and abilities of faculty in the Latin American university context. A quantitative study was developed with a descriptive cross-sectional design and non-experimental field. A self-administered questionnaire was applied to professors with more than 15 years of experience in six national and international universities. The results of the study indicated the presence of four positive factors, one risk factor and one negative factor. The relevance of the factors was obtained by means of statistical metrics proposed in the study. The results revealed that careful and measured planning in the training of new educational tools for teachers positively stimulates them, in addition to mitigating the risk and overcoming the negative phase in virtual teaching.
Keywords: Higher Education; blended learning; COVID-19; context university; analytical